2007
DOI: 10.1016/j.jbiomech.2007.06.018
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical model of artery buckling

Abstract: The stability of arteries under blood pressure load is essential to the maintenance of normal arterial function and the loss of stability can lead to tortuosity and kinking that are associated with significant clinical complications. However, mechanical analysis of arterial bent buckling is lacking. To address this issue, this paper presents a biomechanical model of arterial buckling. Using an elastic cylindrical arterial model, the mechanical equations for arterial buckling were developed and the critical buc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
126
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(136 citation statements)
references
References 30 publications
(42 reference statements)
7
126
1
2
Order By: Relevance
“…Although this review focuses on the modeling of LV remodeling post-MI, it is worth mentioning that modeling techniques have been widely applied to other gene regulatory networks, metabolic pathways, cells, and organs [49,[61][62][63][64][65][66]. However, integration of multi-scale mathematical models into the whole organ model still needs intensive investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Although this review focuses on the modeling of LV remodeling post-MI, it is worth mentioning that modeling techniques have been widely applied to other gene regulatory networks, metabolic pathways, cells, and organs [49,[61][62][63][64][65][66]. However, integration of multi-scale mathematical models into the whole organ model still needs intensive investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, biological tissues are composed of multiple layers of different thicknesses, material properties, and growth rates; e.g. the skin [5], brain [6], artery [7], gut [8], and esophagus [9]. Non-uniform growth results in the appearance of strain mismatch among the layers and leads to the advent of residual stresses [10].…”
Section: Introductionmentioning
confidence: 99%
“…Aorta artery is first mechanically modeled and its stability under blood pressure was studied to determine the critical buckling loads by Han in 2007 [1]. His researches showed that arteries may buckle and become tortuous due to reduced axial strain, hypertensive pressure, and a weakened wall.…”
Section: Introductionmentioning
confidence: 99%